Pembelajaran Bahasa Arab Menggunakan Edmodo di SMP IT Darul Fikri Bengkulu Utara - Annisa Hasanah Irmawansyah; Neli Putri (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
Arabic teaching is rooted in five elements: educational objectives, teaching materials, teaching methods, learning media, and educational evaluation. Information technology that uses it as a learning medium is Edmodo. This study aims to describe learning Arabic using Edmodo. The qualitative method the from descriptive research based on field research. Methods of collecting information related to research from categories by means of interviews, observation, and data analysis. Based on the results of data analysis Arabic learning methods using Edmodo are audio-oral methods, reading methods, dictation methods, grammar, and translation methods. Edmodo Arabic learning media are videos and images. And the evaluation of Edmodo Arabic learning is through a written test containing multiple-choice questions and essay questions. The difficulty of teaching Arabic using Edmodo is that students are late in submitting assignments and don't even do them because the internet is bad or bad, so online learning activities are automatically hampered. so it can be concluded that learning Arabic using Edmodo can be carried out well by teachers and students in participating in Arabic learning remotely.